Simulation a Couple of Exothermic and Endothermic Syngas Processes in a Catalytic Plate Reactor - Safari, Masoud; Towfighi, Jafar; Torkian, Mohammad (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2022)
This paper studies an efficient way to produce syngas from the methane couple reforming and partial methane oxidation by utilizing a catalytic plate reactor. Methane steam and dry reforming as endothermic reactions are coupled with partial methane oxidation as an exothermic reaction in a catalytic plate reactor, which is simulated using detailed reaction kinetics, mass, and energy balances. The impact of inlet temperature, composition, and velocities on the reforming and partial oxidation channels, and also the resulting methane conversions, is studied. In addition, the H2/CO ratio is evaluated for both endothermic and exothermic sides across varied feed ratios. Co- and counter-flow arrangements are simulated for catalytic plate reactors, and their impact on temperature distribution and methane conversion is studied. The suitable plate dimensions, in particular, plate length, are computed during this simulation. Applying a metal plate, Co- and counter-flow arrangements are simulated for catalytic plate reactors, and their impact on temperature distribution and methane conversion is studied. During this simulation, the appropriate plate dimensions, particularly plate length, are determined. The use of a metal plate with a greater thermal conductivity allows for effective heat transmission between endothermic and exothermic channels, resulting in outstanding temperature distribution and slight temperature differences.